Need for high quality worldwide dissemination of our scientific results - Josefa Dolores Miranda Tarragó; Alain Manuel Chaple Gil (Editorial Ciencias Médicas, 2018)
Scientific communication pursues the objective of favoring the dissemination and exchange of research results; the way to achieve it is the scientific publication that must go a long way: from writing the manuscript, selecting the appropriate journal, passing the arbitration and, finally, submitting to the editorial process before publishing; what is described in a few words is very laborious. In our times the interest of the professionals has increased to publish the results of their investigations; all this motivated by communicating the results of the research, obtaining recognition, moving to a higher category, responding to pressure from institutions, among others; but the experience and prestige of the Cuban stomatology is not yet reflected in the publications, there are reports that say so. When the author has selected the journal, he should carefully study the guidelines for authors; in our magazine they are quite explanatory and with following them step by step, at least the formal aspect of the article is achieved; However, sometimes this does not happen, many authors do not take them into account and 80% of the articles before sending them to arbitration are rejected. Some may seem like a very drastic measure, but it is based on the fact that non-compliance with the aforementioned guidelines makes it difficult not only for the arbitrators to work from a scientific point of view, but also for the editorial process. Among the most frequent errors found before sending the articles to arbitration are: unstructured summary, excess of words as well as tables and figures, as well as the recommended size of the latter, outdated bibliographic references, among others. Once the article is submitted to arbitration, it is rigorous and discouraging for authors who receive the signs with displeasure, without realizing that the arbitrators work in an unrecognized and anonymous way, so that the article has greater quality and transparency. Stomatologists must understand that the basic standards agreed upon globally by the scientific editors of biomedical journals are becoming more rigorous every day, so we are committed to increasing our publications with high quality in order to expose the work we carry out in Cuba to the world scientific community. in the world for the sake of oral health.